Storytelling as strategy to promote vocabulary acquisition on third graders. (2016)
The main purpose of the present research was to determine the impact of storytelling as strategy to promote vocabulary acquisition on third graders. This research was carried out in a public school in Armenia, Colombia with a masculine group of fifteen students between seven and nine years old. The design used was action research and the approach was qualitative, however it was necessary to utilize statistics, a quantitative tool. In the course of the investigation the researchers elaborated two stories with specific vocabulary based on El plan de área municipal de inglés (PAMI) and students’ likes. Then, during the English classes it was implemented the storytelling strategy. Through this, data was collected and analyzed too. In which was concluded, that storytelling is an effective, joyful and versatile strategy to contribute on children's vocabulary acquisition process.